The Influence of the Quantum Quotient Strategy in Improving Students' Islamic Learning Achievement at SDN Magetan 1 - Mulyanto, Nanang (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
In the Quantum Quotient technique which can increase students' IQ, EQ and SQ. Among them are various stages related to IQ, EQ and SQ, including helping memory, right brain function because children are trained to imagine, make songs, and combine words so that a material becomes unique, interesting and fun. Meanwhile, the problems taken are how to apply the Quantum Quotient strategy in PAI subjects, how student learning achievement in PAI subjects, is there an influence of the Quantum Quontient strategy in improving student PAI achievement at SDN Magetan 1. This research is a type of quantitative research with a deductive approach, or the methods used are observation, interview, dequmentation, and questionnaire. While the analysis used is static data analysis. From the observation results of the application of the Quantum Quontient strategy, the predicate is good with a number of 82.55 as for the learning achievement of grade 4 students of SDN Magetan 1 with the number 7.9, this shows that the learning outcomes are included in the good category while to prove the influence of the Quantum strategy Quontient in improving the learning achievement of Islamic religious education students, this is proven by the results of the analysis of statistical data